Pengembangan Multimedia Flash pada Materi Energi untuk Meningkatkan Motivasi Belajar Siswa - Riska Purnamasari; Sukainil Ahzan; Baiq Azmi Sukroyanti (Lensa: Jurnal Kependidikan Fisika, 2017)
[Title: Development of Flash Multimedia on Energy Materials to Improve Student Learning Motivation]. This study aims to develop flash multimedia on energy materials to improve student learning motivation. This study is a development research with ADDIE model. Flash multimedia validation involves 2 validators (media experts and media design experts). Validation results show on the aspect of the material with a score of 3.6 with the category "high validity" and the media aspect with a score of 3.4 with the category "high validity". The flash multimedia implementation (trial run) conducted on the 28 students of grade VIII in SMP Negeri 1 Lenangguar, Sumbawa. The results of the implementation showed the students 'motivation before using flash media with the average score of 2.47 with the category "less agree", and after using flash media with average score 3.41 with category "very agree". So it show an increase of student learning motivation. Thus the developement of flash media have eligibility to be used as a medium in learning physics of energy subject matter